2018
DOI: 10.1186/s13046-018-0773-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction of STAT1 isoforms with TGF-β receptors leads to functional crosstalk between two signaling pathways in epithelial ovarian cancer

Abstract: BackgroundThe signal transducer and activator of transcription (STAT) and transforming growth factor-β (TGF-β) signaling pathways play important roles in epithelial ovarian cancer (EOC). However, the mechanism of crosstalk between two pathways is not completely understood.MethodsThe expression of STAT1 protein was detected by tissue microarray and immunoblotting (IB). The interaction of STAT1 isoforms with TGF-β receptors was confirmed by immunoprecipitation and IB. The effect of TGF-β signaling on STAT1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…with TβRI/TβRII suppresses the inducible effects of TGF-β on Smad2 shown in ovarian cancer. STAT1 activation is induced by IFN-γ (Tian et al, 2018), and, as it was aforementioned, IFN-γ production is repressed by TGF-β (Y. Wang, Chu et al, 2018).…”
Section: Stat1 Induces Transcription Of Smad7 Interaction Between Stat1mentioning
confidence: 85%
“…with TβRI/TβRII suppresses the inducible effects of TGF-β on Smad2 shown in ovarian cancer. STAT1 activation is induced by IFN-γ (Tian et al, 2018), and, as it was aforementioned, IFN-γ production is repressed by TGF-β (Y. Wang, Chu et al, 2018).…”
Section: Stat1 Induces Transcription Of Smad7 Interaction Between Stat1mentioning
confidence: 85%
“…High level of STAT1 is associated with improved chemotherapy response in high-grade serous OC, suggesting that STAT1 may be a biomarker of chemosensitivity [16]. Our previous study demonstrated the overexpression of STAT1 in high-grade serous OC and unveiled crosstalk between STAT1 and TGF-β signaling pathways in OC cells [17]. It has been shown that the TGF-β signaling pathway is one of the primary signaling pathways responsible for maintaining pluripotency and self-renewal abilities in embryonic and somatic stem cells [18,19].…”
Section: Introductionmentioning
confidence: 93%
“…The STAT1-overexpressing plasmid was generated in this laboratory as described in our previous report. [17] STAT1-siRNAs were synthesized from GenePharma (Shanghai, China) and the sequences were listed in Supplementary Table 1. Briefly, after seeding in 6-well plates for 24 h, cells were transfected with 5 nM siRNA or 2.5 μg STAT1 plasmid for 6 h. After removing transfection reagents, cells were further incubated for 48 h. The transfected cells were lysed for mRNA and protein extraction or further used for sphere or colony formation assays.…”
Section: Cell Transfection Of Sirna and Plasmidmentioning
confidence: 99%
“…The biological function of STAT1 is still controversial and unclear. Studies of breast (Hou et al, 2018) and ovarian cancer (Tian et al, 2018) found that STAT1 is overexpressed in malignant tumors and plays an oncogenic role. However, studies on colorectal cancer (Crncec et al, 2018) and other breast cancers (Varikuti et al, 2017) found that TAT1 may act as a tumor suppressor.…”
Section: Identification Of Differentially Expressed Tfs and Constructmentioning
confidence: 99%